Digital @ Scale - Swaminathan, Anand; Meffert, Jurgen (Ascent Audio, 2018)
Value in the next phase of the digital era will go to those companies that don't just try digital but also scale it. Digital@Scale examines what it takes for companies to break through the gravitational pull of their legacy organizations and capture the full value of digital. Digging into more than fifty detailed case studies and years of McKinsey experience and data, the authors, along with a group of expert contributors, show how companies can move beyond incremental change to transform the business where the greatest value is generated-at its core. The authors provide practical insights into the three pillars of digital transformations that successfully scale: reinventing the business model, building out a business architecture from the customer back into the organization, and establishing an 'amoeba' IT and organizational foundation that learns and evolves. This is the ideal guide for all leaders who recognize the power and promise of a digital transformation.